2022
DOI: 10.1038/s41419-022-05033-y
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic initiation factor 5A2 mediates hypoxia-induced autophagy and cisplatin resistance

Abstract: Hypoxia-induced cisplatin resistance is a major challenge during non-small cell lung cancer (NSCLC) treatment. Based on previous studies, we further explored the effect of eukaryotic initiation factor 5A2 (eIF5A2) in hypoxia-induced cisplatin resistance. In this study, we found that autophagy and cisplatin resistance were increased under hypoxic conditions in three different NSCLC cell lines. Compared with that under normoxic conditions, dramatic upregulation of eIF5A2 and hypoxia inducible factor 1 subunit al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…Autophagy, an evolutionarily conserved degradation process, is closely associated with the cellular stress response. Several studies have focused on the impact of hypoxia‐induced autophagy in cancer cells (Xu et al, 2022). Hypoxia‐induced HIF1α activation regulates the expression of genes, including BNIP3 and BNIP3L , that are involved in glucose metabolism, angiogenesis, and autophagy (X. Li et al, 2019; Zhao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy, an evolutionarily conserved degradation process, is closely associated with the cellular stress response. Several studies have focused on the impact of hypoxia‐induced autophagy in cancer cells (Xu et al, 2022). Hypoxia‐induced HIF1α activation regulates the expression of genes, including BNIP3 and BNIP3L , that are involved in glucose metabolism, angiogenesis, and autophagy (X. Li et al, 2019; Zhao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…111 Xu et al found that overexpression of eukaryotic initiation factor 5A2 (eIF5A2) is connected to hypoxia-induced autophagy during cisplatin resistance. 112 Therefore, combining eIF5A2 targeted therapy with cisplatin chemotherapy may be a viable approach for treating hypoxia-induced cisplatin resistance and preventing the growth of NSCLC. Liu et al found that hypoxic conditions resulted in an elevated level in xeroderma pigmentosum group C, a crucial DNA damage recognition protein associated with nucleotide excision repair, which helped to cause cisplatin resistance.…”
Section: Hypoxia-induced Impediments In Tumor Treatmentmentioning
confidence: 99%
“…Moreover, hypoxia-induced overexpression of PKM2 reprogrammed cancer-associated fibroblasts (CAFs) to create an acidic TME encouraging the growth and cisplatin resistance of NSCLC cells . Xu et al found that overexpression of eukaryotic initiation factor 5A2 (eIF5A2) is connected to hypoxia-induced autophagy during cisplatin resistance . Therefore, combining eIF5A2 targeted therapy with cisplatin chemotherapy may be a viable approach for treating hypoxia-induced cisplatin resistance and preventing the growth of NSCLC.…”
Section: Hypoxia-induced Impediments In Tumor Treatmentmentioning
confidence: 99%
“…The development of DDP‐resistance is accompanied by a series of abnormal gene expressions. For example, overexpression of eIF5A2 was associated with DDP‐resistance in lung cancer (Xu et al, 2022). Likewise, overexpression of REG4 contributed to DDP‐resistance in ovarian cancer (Xiang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The development of DDP-resistance is accompanied by a series of abnormal gene expressions. For example, overexpression of eIF5A2 was associated with DDP-resistance in lung cancer (Xu et al, 2022).…”
mentioning
confidence: 99%